2021
DOI: 10.1111/hiv.13138
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal status, age and management among women living with HIV in the UK

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…We observed that many women living with HIV answered "don't know" to questions about menopause phase or timing, a finding that may reflect low health literacy of reproductive midlife changes and need for education in this area. Similarly, a low awareness of MHT, which has been previously described among women living with HIV, 16 may make women less inclined to bring up symptoms of menopause. Lack of care provider confidence in menopause management is also likely contributing to these low rates of discussion because a past study reported that 96% of primary care providers (85 of 88) surveyed in the United Kingdom had concerns about managing menopause in the context of HIV.…”
Section: Discussionmentioning
confidence: 94%
“…We observed that many women living with HIV answered "don't know" to questions about menopause phase or timing, a finding that may reflect low health literacy of reproductive midlife changes and need for education in this area. Similarly, a low awareness of MHT, which has been previously described among women living with HIV, 16 may make women less inclined to bring up symptoms of menopause. Lack of care provider confidence in menopause management is also likely contributing to these low rates of discussion because a past study reported that 96% of primary care providers (85 of 88) surveyed in the United Kingdom had concerns about managing menopause in the context of HIV.…”
Section: Discussionmentioning
confidence: 94%
“… 28 Among women with HIV, it has been reported that the prevalence of menopausal symptoms is high and includes hot flushes, pain, mood changes, fatigue and sleep disturbance. 8 , 9 , 29 31 With further evidence to suggest that the severity of vasomotor and psychological symptoms of menopause is greater in women living with HIV than those without. 32 , 33 Although we know that hormone replacement therapy (HRT) and topical vaginal oestrogens alleviate menopausal symptoms and improve women’s HR-QoL, 34 , 35 use of both treatment modalities remains low among women living with HIV, as has been previously reported in the PRIME study.…”
Section: Discussionmentioning
confidence: 99%
“…For each symptom, perceived severity was scored on a Likert-type scale from 0 ( symptoms not present ) to 4 ( very severe ). A composite score was calculated by summing the scores and was categorized as: no/few (0–4), mild , 5 8 moderate 9 16 and severe (⩾ 17) symptoms. 19 …”
Section: Methodsmentioning
confidence: 99%
“…For each symptom, perceived severity was scored on a Likert scale from 0 (symptom not present) to 4 (very severe). A composite score was calculated by summing the scores and categorized as: no/few (0–4), mild [ 5 8 ], moderate [ 9 – 16 ] and severe symptoms (≥ 17) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…As greater numbers of women with HIV reach midlife, evidence has accrued to suggest a high prevalence of menopausal symptoms in this population [ 5 9 ], with these symptoms potentially being more severe than in the general population [ 10 , 11 ]. It is essential that women with HIV are aware of menopause and its associated symptoms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%